2006
DOI: 10.1159/000093315
|View full text |Cite
|
Sign up to set email alerts
|

Association of Estrogen Receptor α (ESR1) <i>Pvu</i>II and <i>Xba</i>I Polymorphisms with Sporadic Alzheimer’s Disease and Their Effect on Apolipoprotein E Concentrations

Abstract: Background: Many studies have shown that estrogen replacement therapy may improve cognitive function in women and reduce the risk of Alzheimer’s disease (AD). Because most of the estrogen neuroprotective effect is mediated by receptors, we studied the associations between estrogen receptor α (ESR1) polymorphisms (PvuII and XbaI) and AD, and their interactions with apolipoprotein E (APOE) polymorphism and plasma levels. Methods: ESR1 genotypes and APOE plasma concentrations were determined in a sample of AD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 51 publications
5
62
2
Order By: Relevance
“…Across all women, the Apoe-ε4 allele was associated with a highly significant 1.9 times increased risk (p<0.0001), however in women with the CC genotype, the risk of AD with the Apoe-ε4 allele increased to 3.2-fold (p<0.0001). This observation is supported by findings from two case-control studies [8,9], which grouped participants based on their ESR1 and ApoE-ε4…”
Section: Ryan 12supporting
confidence: 64%
See 4 more Smart Citations
“…Across all women, the Apoe-ε4 allele was associated with a highly significant 1.9 times increased risk (p<0.0001), however in women with the CC genotype, the risk of AD with the Apoe-ε4 allele increased to 3.2-fold (p<0.0001). This observation is supported by findings from two case-control studies [8,9], which grouped participants based on their ESR1 and ApoE-ε4…”
Section: Ryan 12supporting
confidence: 64%
“…The direction of these associations is supported by a majority of significant case-control studies [8][9][10][11]37], although several prior studies have reported larger effect sizes in smaller samples. These differences may be partly explained by the populations studied, as the majority of significant findings have been found in Japanese populations [10,11,37].…”
Section: Ryan 10mentioning
confidence: 84%
See 3 more Smart Citations